Sportonomics - The Influence of Money to the Sports - Shekjerov, Paskal (2013)
In this master thesis the main focus is directed towards the analysis of the interconnection between the sports and the economics from several different aspects and their interdependence of each other. This was enabled by the introduction of the concept of "Sportonomics", with the main concern on the relationship between the money and the sports, by taking into account different perspectives, such as the direct influence of money to the success, the growing significance of the financial component to the sports, analyzed through the comparisons between leagues (clubs) across the continent including their financial construction, then covering the commercialization of the sports and the on-going movements as an opposition to this trend of commercialization of the sport. Regarding the structure of the thesis and its chapters, in the first chapter it starts off with the most unattractive sport among the ones covered in the thesis by focusing on the financial strength and the actual performances of the clubs in some of the strongest domestic handball competitions in Europe (Bundesliga, ASOBAL, Division 1, Elitserien), as well as including an overview over the emerging new forces from Eastern Europe and the increasing competitiveness posed to the established Western European clubs. In the second chapter, as it moves on towards the sports enjoying higher degree of popularity and investments, there is the basketball game as the main subject of analysis. This part provides an overview of the situation on club and individual (player) level for both the Euroleague and the NBA, as well as clarification of the "salary cap" policy in terms of the limited spending on players' salaries within one team. The last chapter in the thesis, concentrates on the most popular and the most capital intensive sport, the football, with it attracting lots of investors and lots of money being circulated throughout this "market".